Keefektifan Pembelajaran Fisika dengan Pendekatan STEM untuk Meningkatkan Kreativitas Mahasiswa - Joko Siswanto (Jurnal Penelitian Pembelajaran Fisika, 2018)
This study aims to analyze the effectiveness of physics learning with the STEM (Science, Technology, Engineering, and Mathematics) approach to improve student creativity. The research design used was a pre-experiment of one group pre-test and post-test, conducted on 23 students who were taking basic physics at the Universitas PGRI Semarang. The data was collected from the pre-test and post-test of student creativity and observation of the implementation of learning by lecturers and student activities. The creativity test results were analyzed using paired t-test and n-gain to calculate the improvement criteria. The results showed that physics learning with the STEM approach was effective in increasing the creativity of students with moderate criteria. Increased student creativity in basic physics learning with the STEM approach is supported by the implementation of learning as indicated by the activities of lecturers with good criteria and the activities of relevant students in good criteria.